Acceptance and Practice to COVID-19 Vaccination Among Rural Population in Indonesia - Rifda Amalia Choirunnisa; Ede Surya Darmawan (Jurnal Ilmu Kesehatan Masyarakat, 2023)
As one of the strategies to prevent and reduce the spread of COVID-19 since January 2021, the Indonesian Government has implemented a COVID-19 vaccination program. When this research was carried out in the first semester of 2022, the achievement of COVID-19 vaccination target was not yet reach the expected target due to many people were afraid and refused to be vaccinated. The research aims to determine the acceptance and practice of COVID-19 vaccination in rural communities located in Banyumas Regency, Central Java in 2022. This was a cross-sectional study based on electronic survey data distributed to residents (aged ≥ 15 years) of Tunjung Village, Jatilawang Sub-district between May 27, 1 - June 10, 2022. The study sample size was 211 respondents using the quota sampling technique. We used the Health Belief Model (HBM) as the theoretical framework. The research results show that the majority (69%) of respondents stated that they received the COVID-19 vaccination and around 79.6% of those who received it had received the COVID-19 vaccination. Chi-square statistical analysis shows that the variables gender, education, knowledge about COVID-19, knowledge about COVID-19 vaccination, perceived severity of COVID-19, perceived benefits of COVID-19 vaccination, and perceived self-efficacy towards COVID-19 vaccination are related. significantly impact acceptance of COVID-19 vaccination. Perception of self-efficacy towards COVID-19 vaccination is the strongest driving factor for acceptance (POR: 5.45). In the multivariate test, the most dominant variable influencing vaccine acceptance was the variable perception of self-efficacy towards vaccination after controlling for the knowledge variable. A significant relationship was obtained between receipt of COVID-19 vaccination and COVID-19 vaccination practices. It was concluded that acceptance of COVID-19 vaccination is closely related to the level of knowledge and attitudes towards COVID-19 and COVID-19 vaccination, and the higher acceptance encourages the practice of carrying out COVID-19 vaccination. It is recommended that to increase acceptance and practice of Covid vaccination it is necessary to increase the population's knowledge regarding COVID-19 and the COVID-19 vaccine by increasing education and promotion of the COVID-19 vaccination program through electronic media, especially television and social media.